CONCEPTUAL DISTORTION OF SHIRKAH IN INDONESIAN MATRIMONIAL PROPERTY LAW AND ITS IMPLICATIONS FOR THE FARAIDH SYSTEM - Lily Andayani; Indah Dwiprigitaningtias; R. Ardini Rakhmania Ardan (Academic Bright Collaboration, 2026)
This study aims to analyze the forms of conceptual distortion associated with the use of shirkah in the Compilation of Islamic Law and the Marriage Law and to examine their implications for the protection of heirs' rights under the faraidh system. This study employed normative legal research using statute, conceptual, and comparative approaches based on primary, secondary, and tertiary legal materials. The analysis was conducted through normative content analysis, epistemological comparison, and qualitative legal reasoning to evaluate the consistency between Indonesian matrimonial property law and Islamic jurisprudence. The findings reveal four interrelated forms of conceptual distortion terminological, consequential, proportional, and hierarchical—demonstrating that the statutory construction of matrimonial property departs from the contractual principles of authentic shirkah. The analysis further shows that Article 96 of the Compilation of Islamic Law reduces the distributable inheritance estate before the implementation of faraidh, thereby influencing heirs' distributive rights and creating normative tension with the Qur'anic inheritance framework. The findings indicate that the current legal construction of matrimonial property requires conceptual reconstruction through a clearer distinction between shirkah as a contractual institution, contribution-based matrimonial property, and faraidh as a binding inheritance system. Such reconstruction may strengthen legal certainty, improve doctrinal consistency, and better protect heirs' rights within Indonesian Islamic family law. This study is the first to conceptualize the misapplication of shirkah as a multidimensional legal distortion comprising terminological, consequential, proportional, and hierarchical dimensions. It also offers an original analytical framework linking the conceptual misclassification of shirkah directly to measurable distributive consequences in the faraidh system, thereby integrating Islamic contract law, inheritance jurisprudence, and Indonesian matrimonial property law within a unified doctrinal model.